Propuesta de un sistema de control interno con base al informe coso para el área operativa y financiera de la empresa consultora de inmigración a Canadá -Canadasi sociedad civil y comercia - Gualavisí Quishpe, Verónica Elena (2013)
objectives, factors, among others. It also presents individually the components of internal control based on the COSO Report which were used as a basis for the development of the proposed system. The second chapter deals with the general company data such as: the mission, vision, objectives, its organization, the legal basis, among others, and its internal and external analysis to determine your current situation to determine the status of the entity's internal control questionnaires developed, stroke testing, compliance testing, leaf findings, among others. In the third chapter presents the design of the internal control system and financial administration, the same that was developped based on the analysis in the second chapter, taking into consideration the requirements of the entity, by its size and activity.